Evolutionary implications of the distribution and variation of the skeletal muscles of the anuran lymphatic system - Drewes, R.; Hillman, S.; Hedrick, M.; Withers, Philip (Springer, 2013)
Lymphatic return to the circulation in anurans is dependent upon the interaction of a number of skeletal muscles and lung deflation. We define character states and describe variation of these putative lymphatic skeletal muscles: the M. cutaneus pectoris (CP), M. cutaneus dorsi (CD), M. piriformis (P), M. sphincter ani cloacalis (SAC), and the complex of the M. gracilis minor/M. abdominal crenator (GM/AC). We include examination of over 400 specimens of 377 species belonging to 40 of the 42 currently recognized anuran families. Some muscles show limited variation (P) or are clearly linked to phylogeny (CP; CD) and thus have limited value in the determination of form and function. However, the GM/AC and SAC show a high degree of structural variation that appears in taxa across the phylogenetic spectrum. This allows us to make phylogenetically independent determinations of form and function. We define an ancestral state of the GM and conclude that evolution of the GM/AC and SAC has progressed in two directions from this ancestral state: toward either elaboration or reduction. Where present, the character states of both of these muscle groups were observed in all species examined and the number of states correlated within each family as well. The degree of development of the GM/AC and SAC compliance pump system is strongly correlated with previously determined lymph flux rates in a three species test. Our data suggest there may be a relationship between greater elaboration of the GM/AC and SAC system and terrestriality among the Anura. © 2013 The Author(s).